2003
DOI: 10.1680/grim.2003.7.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Stabilising effects of different binders in some Swedish soils

Abstract: In Sweden, lime and lime–cement have been used for several decades as stabilising agents in deep stabilisation of soft soils. More recently, other types of binder have come into use, but so far only to a limited extent. In order to gather experience about the effect of various binders, laboratory tests have been performed on different types of soil stabilised with a range of binders. Lime, cement, fly ash and blast furnace slag in different combinations together with different admixtures, such as gypsum, silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 3 publications
1
18
0
2
Order By: Relevance
“…Many researches were focused on the mechanical qualities of soils reinforced with cement or lime cured in a humid condition [19][20][21][22][23][24][25][26][27][28][29]. However, a large number of factors are known to affect the mechanical properties of treated soils [30].…”
Section: Introductionmentioning
confidence: 99%
“…Many researches were focused on the mechanical qualities of soils reinforced with cement or lime cured in a humid condition [19][20][21][22][23][24][25][26][27][28][29]. However, a large number of factors are known to affect the mechanical properties of treated soils [30].…”
Section: Introductionmentioning
confidence: 99%
“…the water content is lower than the plastic limit. [34] has pointed out that the reduction in water content for the natural soil from around the liquid limit towards the plastic limit is accompanied by an increase in soil strength, which will be discussed later in this study. The effect of Petrit T content and curing time on the soil density is shown in Figure 9.…”
Section: Water Content and Densitymentioning
confidence: 76%
“…The friction angles of mixed soils were compared with the frict ion angles of orig inal soilsas shown in figure (12). According to the results the friction angle has increase for both mixed soils with all used binders however the increase was higher for cement then lime binders than the other used binders.…”
Section: Figure (11) Cohesion Strength From Triaxial and Ucsmentioning
confidence: 97%
“…Taki [9] measured the unconfined compressive strength of different soil types treated with cement. Taki reported that, at the same cement content,coarse grained soil exhibited more increase in strength compared tofine grained soil.Åhnberg [10] studied the stress parameters of cement stabilized soil and concluded that the increase of shear strength is affected by the soil type, the initial water content and by the water/cement ratio.Uddin [11] found that the final compressive strength of the stabilized clay increases with the increase of cement content.Åhnberg [12] studied the difference in strength levels and rate of strength increase between different types of binders" composition and three Swedish soils.The conclusion of the performed unconfined compression tests was that, the optimal b inder composition found for one soil would not be direct ly applicable to another soil as it varies considerably. Åhnberg [13] performed a series of laboratory tests on four soils stabilised with different types of binders to improve the understanding of the strength behaviour of stabilised soils.…”
Section: Introductionmentioning
confidence: 99%